2018
DOI: 10.4081/ijfs.2018.7223
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance, biofilm synthesis and virulence genes in Salmonella isolated from pigs bred on intensive farms

Abstract: Salmonella is the second cause of food-borne infection in humans in the USA and Europe. Pigs represent the second most important reservoir for the pathogen and the consumption of pork meat is a major risk factor for human salmonellosis. Here, we evaluated the virulence patterns of eleven Salmonella isolated from pigs (carcasses and faces) bred in intensive farms in the north of Italy. The two serotypes identified were S. Typhimurium and its monophasic variant 1,4,5,12:i:-. None of the isolates was an ESBL prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
4
15
2
1
Order By: Relevance
“…InvA is a putative inner membrane component of SPI-1, essential for entry into epithelial cells, and it is a specific target gene for confirmation of Salmonella spp. , while hilA is a transcriptional activator essential for the regulation of the invasion process , All the Salmonella tested were positive for both invA and hilA genes, show the virulence potential of the strains in relation to their ability to be invasive after the attachment to the intestinal epithelium (Barrilli et al, 2018) and this coincides with the result in this study as invA was detected as 100% while hilA was 90.9% as in (table3) (fig.,1) and (fig.,4). This was as similar as all the isolates were positive for at least five virulence-related-genes (invA, hilA, stn, ssrA, sipC).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…InvA is a putative inner membrane component of SPI-1, essential for entry into epithelial cells, and it is a specific target gene for confirmation of Salmonella spp. , while hilA is a transcriptional activator essential for the regulation of the invasion process , All the Salmonella tested were positive for both invA and hilA genes, show the virulence potential of the strains in relation to their ability to be invasive after the attachment to the intestinal epithelium (Barrilli et al, 2018) and this coincides with the result in this study as invA was detected as 100% while hilA was 90.9% as in (table3) (fig.,1) and (fig.,4). This was as similar as all the isolates were positive for at least five virulence-related-genes (invA, hilA, stn, ssrA, sipC).…”
Section: Discussionsupporting
confidence: 87%
“…This was as similar as all the isolates were positive for at least five virulence-related-genes (invA, hilA, stn, ssrA, sipC). The same phenomenon has been highlighted in S. typhimurium isolated in swine, where all the strains analysed were positive for sipA, sipD, flgK, flgL,fljB, invA, sopB and sopE2 genes (Barrilli et al, 2018).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is plausible that differences in the determinates of the ability to adhere within the gastrointestinal tract might help explain some of the differences observed in pathogenicity within the swine host. However, several genes known to be involved in virulence, including sipC which is involved in cell adhesion and invasion, sopB which promotes the influx of inflammatory cells and fluid secretion involved in diarrhea, and hilA which activates the invasion process (37), were found to be present in all isolates sequenced including S. Derby.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a study of 133 monophasic isolates showed that the majority possessed the ability to form biofilms (35); this could enhance the in vivo survivability while reducing the effects of antimicrobials on the bacteria (35,36). Salmonella 4, [5],12:i:-also commonly possesses multiple virulence genes that may contribute to its survival within the host and environment; these genes include but are not limited to sipC which is involved in cell adhesion and invasion, sopB which promotes the influx of inflammatory cells and fluid secretion involved in diarrhea, and hilA which activates the invasion process (37). The combination of biofilm formation, presence of virulence genes involved in pathogenesis, resistance to antimicrobials, and resistance to heavy metals may all function together to provide a selective and competitive advantage to S. 4, [5],12:i:-in swine production.…”
Section: Introductionmentioning
confidence: 99%